Systematic Literature Review: The Development of the Internet of Things (IoT) in the Energy Sector - Jaharudin, Norfidah Binti (Engineering and Technology International Journal, 2023)
This systematic literature review explores the development and application of the Internet of Things (IoT) in the energy sector, highlighting its potential to enhance efficiency and sustainability. Facing challenges like the need for higher efficiency, better resource management, and reduced environmental impact, the energy sector benefits significantly from IoT's innovative solutions. These include smart grids, home and building energy management, and industrial operations optimization, enabling real-time monitoring and control for better renewable energy integration and grid stability. Key findings show that IoT implementations can lead to substantial energy savings and environmental benefits. However, challenges such as data security, interoperability, and high implementation costs must be addressed. This review provides a comprehensive overview of IoT's role in energy efficiency and sustainability, offering insights for researchers, practitioners, and policymakers to develop effective strategies for integrating IoT in addressing global energy challenges.